Design is a job - Monteiro, Mike (Book Apart (Series), 2022)
If you are interested in using design as a tool for good, building a more sustainable and equitable society, creating workplaces where everyone is treated with respect, and doing all of these things while still making a living, this book is for you.--Back cover.